Pescadores e turistas em uma área marinha protegida: uma contribuição ao planejamento da Reserva Extrativista Marinha da Ponta do Corumbau, Bahia - Brasil - Stori, Fernanda Terra (Universidade Federal de São Carlos, 2005)
Marine-coastal areas in the South of Bahia State in Brazil has experimented environmental and social changes, related to the over-exploitation of the fishery stocks and to the overflow of carrying capacity of the bathing resorts. Most of traditional communities are migrating out forced by the oppressive tourism economy, leaving fishery and facing cultural and social conflicts. A Marine Protected Area called Ponta do Corumbau Marine Extractive Reserve (or Corumbau Resex) was created in the year 2000, with the aim of sustainability of artisanal fisheries against predatory industrial activity, and to protect a rich biodiversity. The present research has as main objective to contribute to the planning of tourism in this Marine Protected Area through identification of potentialities and conflicts, social and ecological, of tourism activity in the tree studied villages: Cumuruxatiba, Corumbau e Caraíva. There were applied 157 semi-structured questionnaires between tourists and extractivists (fishermen) allowing to investigate the perception of the region and its context in two points of view. The scenic beauty, an opportunity of resting and freedom as well as local receptivity were appointed as the main potentialities by the interviewed tourists. Speculation for land property was identified as motive of conflicts on social relations and extractive culture. Other problems, mostly related to the infrastructure from the villages were also identified. Most of the interviewed extrativists (45% in Cumuruxatiba, 55% in Corumbau and 85% in Caraíva) are nowadays involved with tourism activities. It was possible to note that an initial period of visitation was occurred in the end of seventies and the tourist activity on the tree villages was identified in transition between the Involvement stage to Development, according to Butler (1980). In the same way, according to Smith (1991), Corumbau was identified as Resort Established and Cumuruxatiba and Caraíva as Business Area Established. Such results shows the necessity to control the tourism growing and to an adequate planning of this activity, aiming to link conservation of natural resources, social and economic benefits to extractive communities and the valorization of the artisanal fishery system, the main reason of the Corumbau Resex creation.
Keywords: Ecologia humana; Unidades de conservação; Turismo; Pesca artesanal; Gerenciamento costeiro; CIENCIAS BIOLOGICAS::ECOLOGIA